An Empirical Constitutive Correlation for Regular Jugged Discontinuity of Rock Surfaces (Advances in Applied Mathematics and Mechanics, 2013)
This paper presents a physical investigation and mathematicalanalysis on mechanical behavior of the regular jugged discontinuity.In particular, we focus on the creep property of structural plane withvarious slope angles under different normal stress through shear creeptests of structural plane under shear stresses. According to the testresults, the shear creep property of structural plane was described andthe creep velocity and long-term strength of the structural plane duringshear creep were also investigated. An empirical formula is finally establishedto evaluate shear strength of discontinuity and a modified Burger model wasproposed to represent the shear deformation property during creep.